The Fig - Peter C. Andersen; Timothy E. Crocker (EDIS, 2009)
Revised! HS-27, a 5-page fact sheet by Peter C. Andersen and Timothy E. Crocker, provides the history of fig cultivation, adaptation, description of the fig tree, its culture and management, pests, and fig cultivars. Published by the UF Department of Horticultural Sciences, November 2009.